“There is no place like home”: A Derridean analysis of Rushdie’s conceptualisation of “home” in “At the Auction of the Ruby Slippers” - Ayyıldız, Nilay Erdem (My University, 2020)
Salman Rushdie (1947?) is one of the prominent postcolonial authors writing in a postmodern style. East, West (1992), which is one of his short story collections, problematizes logocentric binaries. “At the Auction of Ruby Slippers” is one of the stories in the collection. The story is a magical realist work based on the movie The Wizard of Oz (1939), which was adapted from L. F. Baum’s children’s fantasy novel The Wonderful Wizard of Oz (1900) depicting little girl Dorothy’s, first, aspiration to migrate from her homeland Kansas, then her struggle to return there, leaving the idyllic atmosphere, new friendships and good experiences in the host land Oz. The story, set in the auction of the slippers, which take Dorothy back to Kansas, tells about the narrator and the other characters’ quest for “home”. The study argues that the story parodies the postcolonial concept of “home” which refers to the native country for immigrants. Moreover, it suggests that the story reconceptualizes the concept of “home”, indicating that it has lost its meaning as a physical or cultural space in a dystopian capitalist society in contrast to the fantasy world of Oz, which enables Dorothy to return her house. Therefore, the postmodern story is examined within the framework of Jacques Derrida’s terms such as “archive”, “différance” and “supplementary” in addition to Rushdie’s essays on the movie. The analysis of the story reveals the play of significations in the conceptuality of “home”. It indicates how the story decentres the signified “home” in Baum’s novel within the postponement of an ultimate signifier and signified. Thus, this study concludes that inhabitants of the multicultural materialistic world are indeed exiles longing and desperately searching for “home”, which is an ever-changing relative metaphor for everything they are deprived of and cannot just attain through materiality in their lives.
Keywords: Edebiyat; Edebi Teori ve Eleştiri